Conservation management strategy impacts inbreeding and mutation load in scimitar-horned oryx - Humble, Emily; Stoffel, Martin A.; Dicks, Kara; Ball, Alex D.; Gooley, Rebecca M.; Chuven, Justin; Pusey, Ricardo; Remeithi, Mohammed Al; Koepfli, Klaus-Peter; Pukazhenthi, Budhan; Senn, Helen; Ogden, Rob (Proceedings of the National Academy of Sciences - PNAS, 2023)
In an age of habitat loss and overexploitation, small populations, both captive and wild, are increasingly facing the effects of isolation and inbreeding. Genetic management has therefore become a vital tool for ensuring population viability. However, little is known about how the type and intensity of intervention shape the genomic landscape of inbreeding and mutation load. We address this using whole-genome sequence data of the scimitar-horned oryx ( Oryx dammah ), an iconic antelope that has been subject to contrasting management strategies since it was declared extinct in the wild. We show that unmanaged populations are enriched for long runs of homozygosity (ROH) and have significantly higher inbreeding coefficients than managed populations. Additionally, despite the total number of deleterious alleles being similar across management strategies, the burden of homozygous deleterious genotypes was consistently higher in unmanaged groups. These findings emphasize the risks associated with deleterious mutations through multiple generations of inbreeding. As wildlife management strategies continue to diversify, our study reinforces the importance of maintaining genome-wide variation in vulnerable populations and has direct implications for one of the largest reintroduction attempts in the world.